LAIR‐1 shedding from human fibroblast‐like synoviocytes in rheumatoid arthritis following TNF‐α stimulation - Zhang, Y. (Clin Exp Immunol, 2018)
This study examined the expression of the inhibitory receptor, leucocyte‐associated immunoglobulin (Ig)‐like receptor‐1 (LAIR‐1) in fibroblast‐like synoviocytes (FLS) in rheumatoid arthritis (RA) patients to investigate its potential role in the modulation of inflammatory cytokines, matrix metalloproteinases (MMPs) and invasiveness of synoviocytes. LAIR‐1 expression in synovial tissues from RA patients, osteoarthritis patients and healthy donors was analysed by immunohistochemistry. The membrane‐bound form (mLAIR‐1) was detected by flow cytometry. Factors involved in inflammation and MMP activity in FLS were analysed by quantitative polymerase chain reaction (qPCR). LAIR‐1 expression was higher in the synovia of the RA patients than those of the osteoarthritis patients. Co‐immunostaining of vimentin/LAIR‐1 demonstrated that LAIR‐1 was localized mainly in FLS in the RA patients. Surprisingly, primary FLS isolated from the RA patients had low levels of mLAIR‐1 expression, with cytoplasmic distribution. The extracellular domain of LAIR‐1 was shed from the cell surface in response to tumour necrosis factor (TNF)‐α, and this process could be blocked by serine protease inhibitors. Additional experiments indicated that LAIR‐1 over‐expression reduced FLS invasion considerably, which reduced simultaneously the mRNA levels of interleukin (IL)‐6, IL‐8 and MMP‐13 in the presence of TNF‐α. Our study demonstrated that LAIR‐1 is an anti‐inflammatory molecule, and was up‐regulated in FLS in the RA patients; however, cell‐surface LAIR‐1 could be shed from cells in the inflammatory microenvironment in RA. This may weaken the interaction of LAIR‐1 with its ligand, thus reducing the anti‐inflammatory effects of LAIR‐1. These findings suggested that LAIR‐1 may be an important factor involved in the mediation of the progressive joint destruction in RA.